2004
DOI: 10.1074/jbc.m409657200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metal Ion Binding on the Structural Stability of the Hepatitis C Virus RNA Polymerase

Abstract: The RNA polymerase activity of the hepatitis C virus, a major human pathogen, has previously been shown to be supported by metal ions. In the present study, we report a systematic analysis of the effect of metal ion binding on the structural stability of the hepatitis C virus RNA polymerase. Chemical and thermal denaturation assays revealed that the stability of the protein is increased significantly in the presence of metal ions. Structural analyses clearly established that metal ion binding increases hydroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…Several earlier studies reported different roles for divalent metal ions in the polymerase function (24, 25). We examined the effect of MgCl 2 on the formation of the elongation complex (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several earlier studies reported different roles for divalent metal ions in the polymerase function (24, 25). We examined the effect of MgCl 2 on the formation of the elongation complex (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Based on amino acid similarity within eight distinct RdRp motifs, protein A belongs to the positive-strand RNA RdRp supergroup I (34, 35). The sixth RdRp motif contains a GDD motif that is conserved among RdRps of all positive-strand RNA viruses and is required for metal ion coordination in the polymerase active site (4,9,34,35). Mutation of the GDD motif inhibits polymerase activity in many viruses, such as hepatitis C virus, poliovirus, and FHV (9, 31).…”
mentioning
confidence: 99%
“…17 The three-dimensional structure of 1QUV was determined without metal ions coordinated within the active site. However, two magnesium ions were added to the structure in all simulations because they have been shown biochemically to be needed for efficient enzyme function 18,19 and have been observed to fundamentally alter the structure and dynamics of the enzyme in previous molecular simulations by our group. 15 Two allosteric inhibitors, 3MS and VGI, were employed in this work.…”
Section: Methodsmentioning
confidence: 99%